Салтовская полуземлянка на городище Тиритака - Зинько, В.Н.; Пономарев, Л.Ю. (Материалы по археологии, истории и этнографии Таврии, 2006)
На античном городище Тиритака раннесредневековый горизонт, относящийся ко времени функционирования салтово-маяцкого поселения, был выделен в 30-е гг. XX в. Соответствующие ему слои и жилищнохозяйственные комплексы удалось проследить в 1933-1940, 1946-1952 гг. на раскопах V, VI, X, XIII, XIV, XV, а в северо-восточной и западной части городища были раскопаны одновременные им плитовые и грунтовые могилы . Первоначально В. Ф. Гайдукевич датировал это поселение VII-VIII вв., а позднее отнес его к VIII-IX вв. Однако, в обоих случаях предложенные им хронологические границы основывались не на археологическом материале или же данных стратиграфии, а на господствовавших в разные периоды представлениях о верхней и нижней дате салтово-маяцкой культуры. In 2002 Crimean Department of the Institute of Oriental Studies of National Academy of Sciences of Ukraine together with “Demeter” Fund started an important complex scientific program on the ancient site of Tiritaka. New excavation area XXVI was founded in the central part of the site. The latest horizon is dated back to the period of the existence of Saltovo-Majatsky settlement in Tiritaka in the 8th - the first half of the 10th centuries. During this stage of research we have managed to trace two building periods. Prop-free oval in plan half-dugout hut discovered in the eastern part of excavation area in 2004 belongs to the first one. In Crimea, including Kerch peninsula, Saltovo-Majastsky half-dugout huts are known in many settlements, but they have different construction. Most likely, the date of the construction of half-dugout hut should be dated back to the end of the 8th - the beginning of the centuries and was abandoned not later than in the mid- 9th century. Later, half-filled foundation pit of the hut and the territory adjacent to it were turned into cinder heap which had been functioning in the second half of the 9th - the first half of the 10th centuries.